COVID-19, SARS and MERS: A neurological perspective - Ng Kee Kwong, Koy Chong; Mehta, Puja R.; Shukla, Garima; Mehta, Arpan R. (Journal of clinical neuroscience, 2020)
•COVID-19 is caused by a highly pathogenic coronavirus named “SARS-CoV-2”.•COVID-19 pathophysiology is primarily defined by acute respiratory illness.•Several studies have revealed a possible neurological component to COVID-19.•Various neurological manifestations have also been reported for SARS and MERS.•Further research into the importance of neurological manifestations in COVID-19 is needed. Central to COVID-19 pathophysiology is an acute respiratory infection primarily manifesting as pneumonia. Two months into the COVID-19 outbreak, however, a retrospective study in China involving more than 200 participants revealed a neurological component to COVID-19 in a subset of patients. The observed symptoms, the cause of which remains unclear, included impaired consciousness, skeletal muscle injury and acute cerebrovascular disease, and appeared more frequently in severe disease. Since then, findings from several studies have hinted at various possible neurological outcomes in COVID-19 patients. Here, we review the historical association between neurological complications and highly pathological coronaviruses including SARS-CoV, MERS-CoV and SARS-CoV-2. We draw from evidence derived from past coronavirus outbreaks, noting the similarities and differences between SARS and MERS, and the current COVID-19 pandemic. We end by briefly discussing possible mechanisms by which the coronavirus impacts on the human nervous system, as well as neurology-specific considerations that arise from the repercussions of COVID-19.